SOCIAL SUPPORT AND COGNITIVE IMPAIRMENT IN MEXICAN ORIGIN OLDER ADULTS IN THE U.S. AND MEXICO. (11th November 2018) - Lopez-Ortega, M; Angel, J; Angel, R; Cantu, P
Abstract: Purpose: This study examines living arrangements of older adults with cognitive impairment in the Hispanic-EPESE and the Mexican Health and Aging Study (MHAS). Methods: Our sample includes 1, 072 adults 85 and older from the HEPSE and 1, 521 adults of the same age from the MHAS. We create a typology of living arrangements based on marital status and household size using wave 7 (2010–2011) of the H-EPESE and wave 3 (2012) of the MHAS. Results: Among cognitively impaired community dwelling adults, those in the HEPSE were more likely to live in extended households than those in the MHAS. Cognitively impaired individuals in the MHAS were more likely to be living with a spouse only. In both nations approximately one-fifth of the cognitively impaired live alone. Conclusion: Cognitive impairment is associated with differential living arrangements in Mexico and the U.S. We discuss the policy implications of this growing burden for both nations.